KUALITAS HASIL TERJEMAHAN GOOGLE TRANSLATE DARI BAHASA ARAB KE BAHASA INDONESIA - Khoiriyah, Hidayatul (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2020)
The development of technology has a big impact on human life. The existence of a machine translation is the result of technological advancements that aim to facilitate humans in translating one language into another. The focus of this research is to examine the quality of the google translate machine in terms of vocabulary accuracy, clarity, and reasonableness of meaning. Data of mufradāt taken from several Arabic translation dictionaries, while the text is taken from the phenomenal work of Dr. Aidh Qorni in the book Lā Tahzan. The method used in this research is the translation critic method. The results showed that in terms of the accuracy of vocabulary and terms, Google Translate has a good translation quality. In terms of clarity and reasonableness of meaning, google translate has not been able to transmit ideas from the source language well into the target language. Furthermore, in grammatical, the results of the google translate translation do not have a grammatical arrangement, the results of the google translate translation do not have a good grammatical structure and are by following the rules that applied in the target Indonesian language.From the data, it shows that google translate should not be used as a basis for translating an Arabic text into Indonesian, especially in translating verses of the Qur'ān and Hadīts. A beginner translator should prefer a dictionary rather than using google translate to effort and improve the ability to translate.Key Words: Translation, Google Translate, Arabic